1984
DOI: 10.1002/em.2860060305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for detecting mitomycin C‐ and ethyl nitrosourea‐induced germ cell damage in mice: Sperm enzyme activities, sperm motility, testis weight

Abstract: Testes weights, sperm motility and enzyme activities in single sperm were compared with respect to their ability to detect either developmental or mutational damage to germ cells. Male mice were injected i.p. with 2.5 mg/kg mitomycin C (MC) or 50 or 100 mg/kg ethylnitrosourea (ENU) or saline and were then killed at times such that sperm derived from treated vas sperm (SZ), spermatids (ST), preleptotene-late-spermatogonial cells (PLSG), spermatogonial cells (SG), or spermatogonial stem cells (SGS) could be eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In contrast, preimplantation loss was significantly induced following mating with males treated at 5 x 50 mgkg. Preimplantation losses induced after treatment of spermatogonial stem cells are probably due to oligospermy or non-functioning sperm, reflecting a strong cytotoxic effect by ENU at the stem cell stage [12,13]. In this context, it should be noted that the values for the frequency of preimplantation losses given in Table I are underestimates because the number of corpora lutea was not counted in females with no implants.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, preimplantation loss was significantly induced following mating with males treated at 5 x 50 mgkg. Preimplantation losses induced after treatment of spermatogonial stem cells are probably due to oligospermy or non-functioning sperm, reflecting a strong cytotoxic effect by ENU at the stem cell stage [12,13]. In this context, it should be noted that the values for the frequency of preimplantation losses given in Table I are underestimates because the number of corpora lutea was not counted in females with no implants.…”
Section: Resultsmentioning
confidence: 98%
“…These multifunctional chemicals undoubtedly caused their effects in PLSG cells by a different mechanism than the one by which they affect already developed SZ (Ficsor et al, 1984a). Therefore, it is important to sample at least two populations of germ cells representing pre-and post-meiotic cells, as was done in the present study.…”
Section: -T I mentioning
confidence: 99%
“…Numerous studies have shown that ENU alters spermatogenesis. Ficsor et al (1984) reported altered mouse sperm morphology forty-nine days after a single ip treatment with 100 mg/kg ENU. Skare and Schrotel (1984) have shown DNA single-strand breaks in rat testicular DNA following ip injection of 85.2 mg/kg ENU.…”
Section: Introductionmentioning
confidence: 99%